(untitled) (Polifonia, 2015)
Nesse texto, damos visibilidade a como o discurso da Comunidade de Países de Língua Portuguesa (CPLP) – sustentado no discurso do multilinguismo/culturalismo, pelos dizeres da proteção e da inclusão, e no discurso da lusofonia, pelos dizeres de passado e língua comuns –, (re)produz sentidos que narrativizam as relações entre sujeitos/línguas/espaços como evidentes: todos falam a língua portuguesa; e essa língua, com suas "variações", é a mesma para todos, apesar de suas heterogêneas historicidades, memórias e singularidades em movimento. Para compreender a produção do efeito de homogeneidade, analisamos o funcionamento do nome "lusofonia" no discurso científico-linguístico, em um artigo da Revista Organon (1994). PALAVRAS-CHAVE: línguas portuguesas, lusofonia, CPLP, discurso, memória LUSOPHONY AND THE CPLP: IMPOSSIBILITY OF OTHER IMAGINARIES OF LANGUAGES ABSTRACT: In this text we show how the CPLP’s discourse (Community of Portuguese Language Countries) – based on the multilinguism/culturalism discourse (through the ideas of protection and inclusion), and on the lusophony discourse (through the ideas of common past and language) –, (re)produces sense effects that narratize the relationships among subjects/languages/spaces as evident: everyone speaks the Portuguese language; and that language with its "varieties" is the same for everybody, in spite of their heterogeneous historicities, memories and singularities in movement. To understand the production of the homogeneity effect, we analyze how the noun "lusophony" works in the scientific-linguistic discourse, in a paper published in the Organon journal (1994). KEYWORDS: Portuguese languages, lusophony, CPLP, discourse, memory